Quality of IPB-D1 Chicken Egg Yolk Powder Using Various Drying Methods - Salsabila Ma’shum Imawan; Zakiah Wulandari; Tuti Suryati; Cece Sumantri (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2023)
IPB D-1 chickens had good egg productivity. Chicken eggs are often used as functional ingredients in the form of powder because they have many advantages for the food industry. This research aims to produce egg yolk powder with good physicochemical, microbiological, and fatty acid qualities derived from IPB-D1 chicken eggs using various drying methods namely spray drying, oven drying, and vacuum drying. This study also aims to examine the functional properties of IPB-D1 chicken egg yolk powder by application to mayonnaise. It is compared with mayonnaise made from fresh egg yolks and commercial egg yolk powder. The experimental design used in this research was a randomized block design (RBD) based on the manufacturing period. The result showed that different drying methods for egg yolk powder can affect the emulsion activity, total plate count (TPC), aw, pH, water, ash, and fat content. The drying method did not affect the protein content and emulsion stability. Egg yolk powder with oven drying gave the best results for quality.